T05. Pre-surgical assessment of drug-resistant insular and peri insular epilepsy: A single center experience. (May 2018) - Aldosari, Mubarak; Joswig, Holger; Marti, Ana Suller; McLachlan, Richard; Mirsattari, Seyed M.; Diosy, David C.; Jones, Michelle-Lee; Steven, David; Parrent, Andrew; MacDougall, Keith W.; Burneo, Jorge
Abstract : Introduction: Epilepsy arising from the insula is widely regarded as a challenging type of seizure, probably owing to the deep-seated location of the insula and the extensive connections it makes with adjacent structures. In recent years, we have rapidly gained insights into insular epilepsy-related obstacles. Here, we describe a detailed analysis of the electro-clinical manifestations of this type of epilepsy using intra-cerebral recordings performed with Stereo-electroencephalography (SEEG). Methods: We retrospectively analyzed 12 patients from our epilepsy program who underwent insular exploration using SEEG between June 2013 and June 2017. Patient information reviewed included demographics, clinical history, neurological examination; neuroimaging studies (Brain MRI, PET, Ictal SPECT), Scalp video-EEG, intracranial recordings with SEEG, histopathological findings, and surgical outcomes. Results: 12 patients (M:F = 4:8; mean age, 32.5 years; range, 19–60 years) were found with seizures originating from either the insula alone or simultaneously originating from the insula and adjacent structures. One patient had a family history of epilepsy and another one had previous exposure to viral meningoencephalitis. Six patients had undergone prior surgery for epilepsy treatment. The mean seizure frequency was 4 seizures per week, and one patient experienced seizures daily. The most common aura was somatosensory sensation, followed by cephalic sensation in 4 and 3 patients, respectively. The commonest type of seizure was focal with impaired awareness in 10 patients. 50% of the patients showed a tendency for secondary generalizations, and 25% showed nocturnal predominance. Lesions were observed on brain MRI in 8 cases. Scalp EEG revealed different interictal discharge distributions: 5 patients showed localized frontotemporal spikes, 3 showed bilateral temporal spikes, and no spikes were detected in 4. The location of ictal onset could be localized in only 50% of patients. The most common scalp EEG ictal pattern was rhythmic delta activity (1–3 Hz). Subsequent SEEG showed six patients found to have a combination of clinical and subclinical seizures. SEEG clinical seizure onset from the insula alone was found in 50% of the patients (3 right, 2 left, 1 bilateral). The other patients presented with simultaneous onset from the insula and adjacent structures: 4 from mesial temporal structures, 1 temporal operculum, and 1 frontal operculum. The commonest SEEG ictal pattern was low voltage fast activity in 8 patients. Surgical resections guided by SEEG findings were performed in 5 patients and led to excellent outcomes; all these cases had Engle class 1 outcome at 6–24 months follow up. Conclusion: We observed that it is not uncommon for seizures to simultaneously originate from the insula and adjacent structures. However, non-invasive EEG monitoring tools are likely insufficient to detect such simultaneous seizures. For the given sample, SEEG proved beneficial in providing optimal surgical outcomes.